Manuel Jaramillo Cervilla. 'Maximiano Fernández del Rincón (1835-1907)' - FERNÁNDEZ SEGURA, Francisco José (Boletín del Centro de Estudios «Pedro Suárez», 1997)
Manuel Jaramillo Cervilla. 'Maximiano Fernández del Rincón (1835-1907)'